Natural Macromolecules as Carriers for Essential Oils: From Extraction to Biomedical Application - Dajic Stevanovic, Zora; Sieniawska, Elwira; Glowniak, Kazimierz; Obradovic, Natasa; Pajic-Lijakovic, Ivana (Frontiers in Bioengineering and Biotechnology, 2020)
Essential oils (EOs) and their main constituents, the terpenes, are widely studied, mostly relating their antioxidant ability and bioactivity, such as antimicrobial, anticancer, anti-inflammatory, and range of other actions in the living systems. However, there is limited information on their bioavailability, especially upon clinical studies. Having in mind both strong biological effects and health benefits of EOs and their specific physicochemical properties (volatility, lipophilic character, low water solubility or insolubility, viscosity, expressed odour, concentration-dependent toxicity, etc.), there is a need for their enteric coating for target delivery. Encapsulation of EOs and their constituents is the prerequisite for enhancing their oxidative stability, thermo stability, photostability, shelf-life, and biological activity. We considered various carrier types such as: (1) mono-phase and poly-phase polysaccharide hydrogel carriers, (2) polysaccharide-protein carriers, and (3) lipid carriers in the context of physicochemical and engineering factors. Physicochemical factors are: encapsulation efficiency, chemical stability under gastric conditions, mechanical stability and thermal stability of carrier matrices. Choice of carrier material also determines the encapsulation technique. Consequently, the engineering factors are related to the advantage and disadvantage of various encapsulation techniques frequently used in the literature. In addition, it was intended to address the interactions between: (1) main carrier components as: polysaccharides, proteins and lipids themselves (in order to form chemically and mechanically stable structure), (2) main carrier components with pepsin under gastric conditions (in order to form resistant material under gastric conditions), and (3) main carrier components with essential oils (in order to enhance encapsulation efficiency), as necessary precondition for whole process optimization. Finally, different sources for obtaining natural carrier macromolecules are surveyed, especially the agro-waste materials and agricultural and food by-products. This review paper highlights the bioavailability aspects of encapsulated essential oils and physicochemical and engineering factors concerning natural macromolecule carriers for their target delivery.